The Association of Acceptance Family Planning Acceptor to Contraceptive Tools Interest Usage in the Uterine (IUD) - Rajuddin, Rajuddin; Fauzan, Fauzan (Indonesian Socety of Obstetrics and Gynecology, 2019)
Abstract Objective:to determine acceptance of family planning acceptors from age, numbers ofparity, mother education, spouse’s support, mother's culture and religion, maternalknowledge, gestational age, family income and number of living children to the IUD usage interest in dr. Zainoel Abidin General Hospital (RSUDZA) Banda Aceh. Method: This research wasa correlative design with analytical survey method with cross sectional approach. 286 respondents were interviewed and filled out a questionnaire that has been prepared, consist ofpatients in the clinic, Emergency Unit, and Delivery Room Hospital RSUDZA Banda Aceh. The data taken related tofactors influencing the acceptance of the family planning acceptors against the IUD usage interests. This study was conducted duringSeptember 18 th to October 18 th 2017. Results: The chi-square test result showed that there was a significant correlation between family planning acceptor from previous pregnancy distance and IUD usageinterest in RSUDZA Banda Aceh where p-value (0.088) <α (0.1). There was a significant correlation between maternalknowledgeand IUD usage interest in RSUDZA Banda Aceh where p-value (0.067) <α (0.1). Conclusion: Bivariate analysis results showed there was a strong relationship between previous pregnancy distance and maternal knowledgetoIUD usage interest in RSUDZA Banda Aceh. Keywords:acceptor family planning, acceptance factor, IUD   Abstrak Tujuan:untuk mengetahui hubungan penerimaan akseptor KB dari faktor usia, jumlah paritas, pendidikan ibu, izin suami, budaya dan agama ibu, pengetahuan ibu, jarak usia kehamilan, pendapatan keluarga dan jumlah anak hidup terhadap minat penggunaan AKDR di Rumah Sakit Umum dr. Zainoel Abidin (RSUDZA) Banda Aceh. Metode:Penelitian ini menggunakan desain korelatif dengan metode penelitian survei analitik dengan pendekatan cross sectional. Terdapat 286 responden yang telah diwawancarai dan mengisi kuisioner yang telah disediakan, terdiri dari pasien-pasien di poliklinik, Instalasi Gawat Darurat, dan kamar bersalin RSUDZA Banda Aceh. Data yang diambil mengenai faktor- faktor yang mempengaruhi peneriman akseptor KB terhadap minat penggunaan AKDR. Penelitian ini dilakukan dalam kurun periode tanggal 18 September sampai 18 Oktober 2017. Hasil: uji chi-square menunjukkan terdapat hubungan secara signifikan penerimaan akseptor KB dari faktor jarak kehamilan ibu sebelumnya terhadap minat penggunaan AKDRdimana p-value (0,088) <α (0,1). Terdapat hubungan pengetahuan ibu dengan terhadap minat penggunaan AKDRdi RSUDZA Banda Aceh dengan nilai p-value (0,067) <α (0,1) Kesimpulan: Hasil analisis bivariat didapatkan terdapat hubungan yang kuat antara jarak kehamilan ibu dan pengetahuan ibu terhadap minat penggunaan AKDR di RSUDZA Banda Aceh. Kata kunci: akseptor KB, AKDR, faktor penerimaan